2015
DOI: 10.1063/1.4905681
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-doped 9-cell cavity performance in a test cryomodule for LCLS-II

Abstract: The superconducting RF linac for LCLS-II calls for 1.3 GHz 9-cell cavities with an average intrinsic quality factor Q0 of 2.7×10 10 at 2.0 K and 16 MV/m accelerating gradient. Two niobium 9 cell cavities, prepared with nitrogen-doping at Fermilab, were assembled into the Cornell Horizontal Test Cryomodule (HTC) to test cavity performance in a cryomodule that is very similar to a full LCLS-II cryomodule. The cavities met LCLS-II specifications with an average quench field of 17 MV/m and an average Q0 of 3×10 10… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 9 publications
2
43
0
Order By: Relevance
“…In contrast, high Q 0 accelerator applications generally use multicell cavities in horizontal orientation, with their helium jackets connected together in long strings. Previous experiments 29,30 have shown that in the horizontal cavity orientation, vertical thermal gradients-in this case, perpendicular to the cavity axis-are beneficial to flux expulsion (consistent with what is observed in the experiments presented here). For example, in the upcoming LCLS-II project, 31 a high duty factor accelerator where obtaining high Q 0 is critical to minimizing cryogenic costs, the specification for magnetic field in the cryomodules is 5 mG. As Fig.…”
Section: -4supporting
confidence: 80%
“…In contrast, high Q 0 accelerator applications generally use multicell cavities in horizontal orientation, with their helium jackets connected together in long strings. Previous experiments 29,30 have shown that in the horizontal cavity orientation, vertical thermal gradients-in this case, perpendicular to the cavity axis-are beneficial to flux expulsion (consistent with what is observed in the experiments presented here). For example, in the upcoming LCLS-II project, 31 a high duty factor accelerator where obtaining high Q 0 is critical to minimizing cryogenic costs, the specification for magnetic field in the cryomodules is 5 mG. As Fig.…”
Section: -4supporting
confidence: 80%
“…We calculated the surface resistance at 68 mT (E acc % 16 MV/m for a TESLA cavity), the operating accelerating gradient spec of the Linac Coherent Light Source II (LCLS-II), to compare to experimental data at the 16 MV/m operating gradient and at low field; LCLS-II is a relevant choice for this comparison because it is an SRF-powered continuous-wave free-electron laser under construction at the SLAC National Accelerator Laboratory, using nitrogen-doped 1.3 GHz niobium TESLA cavities. 29,30 Figure 6 shows the low field BCS resistance (normalized in D and T c , as described above) at 21 mT ($5 MV/m), the theoretical BCS resistance for average material parameters, the theoretical BCS resistance at 68 mT calculated from Gurevich's theory 16 and the a 0 ð'Þ model presented here, and the experimental data at 68 mT. We see agreement with the high-field experimental data, and in particular, with the shifted minimum in R BCS as a function of ', to about 17 nm at 68 mT from the low-field minimum of 25 nm for these material parameters.…”
Section: Quasiparticle Overheating and The Mean Free Pathmentioning
confidence: 99%
“…11 Since then, work at Cornell and Fermilab (FNAL) has shown that large spatial temperature gradients are important for maximal flux expulsion during cool down. 12,13 Understanding the dependence of sensitivity of RF losses from trapped flux is crucial now as Q 0 performance and specifications keep increasing. Nearly, all modern cavity preparation techniques use niobium that has a surface RF layer with a lower mean free path than the bulk niobium.…”
mentioning
confidence: 99%